The Pius War : Responses to the Critics of Pius XII. - Bottum, J. (Rowman & Littlefield Pub. Group, 2010)
In the brutal fight that has raged in recent years over the reputation of Pope Pius XIIleader of the Catholic Church during World War II, the Holocaust, and the early years of the Cold Warthe task of defending the Pope has fallen primarily to reviewers. These reviewers formulated a brilliant response to the attack on Pius, but their work was scattered in various newspapers, magazines, and scholarly journalsmaking it nearly impossible for the average reader to gauge the results. In The Pius War, Weekly Standard's Joseph Bottum has joined with Rabbi David G. Dalin to gather a representative an.